Clinical Trials Design in Operative and Non Operative Invasive Procedures - Itani, Kamal M.F; Reda, Domenic J. (Springer International Publishing : Imprint: Springer, 2017)
The aim of this text is to provide the framework for building a clinical trial as it pertains to operative and non operative invasive procedures, how to get it funded and how to conduct such a trial up to publication of results. The text provides all details of building a scientifically and ethically valid proposal, including how to build the infrastructure for a clinical trial and how to move it forward through various funding agencies. The text also presents various types of clinical trials, the use of implantable devices and FDA requirements, and adjuncts to clinical trials and interaction with industry. Clinical Trials Design in Invasive Operative and Non Operative Procedures will be of interest to all specialists of surgery, anesthesiologists, interventional radiologists, gastroenterologists, cardiologists, and pulmonologists.
Keywords: Medicine.; Anesthesiology.; Interventional radiology.; Cardiology.; Surgery.; elektronické knihy; electronic books